STUDY ON MORPHOLOGICAL CHARACTERS OF INDONESIAN LITTER FROG (LEPTOBRACHIUM, MEGOPHRYIDAE) - Fauzan, Muhammad Fakhri; Farajallah, Achmad; Hamidy, Amir (Treubia, 2025)
Leptobrachium from Southeast Asian populations previously were recognized as a single species Leptobrachium hasseltii Tschudi. Taxonomic reassessment revealed that Leptobrachium consists of some cryptic species due to similarities in their morphological appearance but diverse in molecular characters. Among the Indonesian populations, Leptobrachium was split into seven species (L. hasseltii, L. nigrops, L. waysepuntiense, L. hendricksoni, L. ingeri, L. abbotti, and L. montanum). Specifically, L. hasseltii is separated into two groups; the Sumatran-Javan and the Bali populations. In this study, we analyzed the morphological data of 100 individuals of Leptobrachium to evaluate their morphological differences. The morphological differences expressed by analysis of variance (ANOVA) and principal component analysis (PCA) revealed significant differences between each Leptobrachium and four morphological characters suitable for species identification (the iris color, color pattern, humeral and femoral gland). The morphological differences also showed that the Bali population probably is undescribed species.